2012
DOI: 10.1039/c1nj20790c
|View full text |Cite
|
Sign up to set email alerts
|

Bis-porphyrin copolymers covalently linked by pyridinium spacers obtained by electropolymerization from β-octaethylporphyrins and pyridyl-substituted porphyrins

Abstract: Five bis-porphyrin copolymers have been obtained by an electropolymerization process using zinc b-octaethylporphyrin (ZnOEP) type macrocycles and porphyrins functionalized by several pyridyl groups. This electropolymerization process is based on a nucleophilic attack of the pyridyl groups onto electrogenerated ZnOEP dications at their meso-positions. It is the first time that bis-porphyrin copolymers have been obtained. In this study, the copolymers have been characterized by electrochemistry, UV-visible absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…They also showed that couplings between pyridinium units on the free base porphyrins occurred but did not occur through the zinc octaethylporphyrins. 22 Walter and Wamser reported an oxidatively electropolymerized tetraaminophenylporphyrin (Fig. 6).…”
Section: Types Of Porphyrin Polymers and Preparative Methodsmentioning
confidence: 98%
“…They also showed that couplings between pyridinium units on the free base porphyrins occurred but did not occur through the zinc octaethylporphyrins. 22 Walter and Wamser reported an oxidatively electropolymerized tetraaminophenylporphyrin (Fig. 6).…”
Section: Types Of Porphyrin Polymers and Preparative Methodsmentioning
confidence: 98%
“…Thus, Ruhlmann and coworkers used dipyridyldiphenylporphyrins in the presence of (OEP)Zn and obtained copolymers having two different kinds of perfectly alternating macrocycles (see Figure 28A). 142 This method of electropolymerization appears to be the simplest allowing the formation of bis-porphyrin copolymers.…”
Section: Formation Of Bis-porphyrin Copolymersmentioning
confidence: 99%
“…In order to permit better control of the geometry of the polymers, (OEP)Zn macrocycles substituted by two protecting groups such as chlorides (see Figure 27B) 130,142 or pyridiniums 136 were used. In these cases, linear wires of polymers were obtained.…”
Section: Formation Of Linear Polymeric Chainsmentioning
confidence: 99%
“…One should note that an advantageous feature of these copolymers is that the spacer present between macrocycles is shorter than previously in polymerization used bipyridinium or py-Tz-py units, since here only pyridinium groups serve for linking of two macrocycles [69].…”
Section: Zinc(ii) Porphyrins With Electrochemical Propertiesmentioning
confidence: 99%